Association Between Lipoprotein(a) and Calcific Aortic Valve Disease: A Systematic Review and Meta-Analysis - Liu, Qiyu; Yu, Yanqiao; Xi, Ruixi; Li, Jingen; Lai, Runmin; Wang, Tongxin; Fan, Yixuan; Zhang, Zihao; Xu, Hao; Ju, Jianqing (Frontiers in Cardiovascular Medicine, 2022)
Background: Preliminary studies indicated that enhanced plasma levels of lipoprotein(a) (lp(a)) might link with the risk of calcific aortic valve disease (CAVD), but the clinical association between them remained inconclusive. This systematic review and meta-analysis were aimed to determine this association. Methods: We comprehensively searched PubMed, Embase, Web of Science and Scopus databases for studies reporting the incidence of CAVD and their plasma lp(a) concentrations. Pooled risk ratio (RR) and 95% confidence interval (95% CI) were calculated to evaluate the effect of lp(a) on CAVD using the random-effects model. Subgroup analyses by study types, countries and the level of adjustment were also conducted. Funnel plots, Egger’s test and Begg’s test were conducted to evaluate the publication bias. Results: Eight eligible studies with 52931 participants were included in this systematic review and meta-analysis. Of these, four were cohort studies and four were case-control studies. Five studies were rated as high quality, three as moderate quality. The pooled results showed that plasma lp(a) levels ≥ 50 mg/dL were associated with a 1.76-fold increased risk of CAVD (RR, 1.76; 95% CI, 1.47-2.11), but lp(a) levels ≥30 mg/dL were not observed to be significantly related with CAVD (RR, 1.28; 95% CI, 0.98-1.68). The pooled RR of cohort studies in lp(a) 50 mg/dL group was 1.70 (95% CI, 1.39-2.07), in lp(a) 30 mg/dL group was 1.38 (95% CI, 1.19-1.61). Conclusion: High plasma lp(a) levels (≥50 mg/dL) are significantly associated with increased risk of CAVD.